THE EFFECT OF MYOPIC DERIVATIVES OF ESTABLISHED HYBRID RICE SEEDS P 05 AND CEMETI INBRED RICE SEEDS AT VARIOUS PLANTING DISTANCES ON PLANT PHENOTYPE - Novita Restiani Novita; RR. Siti Astuti; Suharno Suharno (Politeknik Pertanian Negeri Samarinda, 2022)
This study aims to determine the effect of ratoon derivatives of hybrid rice seeds (Mapan P-05) and Inbred rice seeds (Cemeti) at various spacings on the diversity of plant phenotypes. This research was carried out in Sumberharjo Prambanan Village, Sleman Yogyakarta. The method used was a factorial complete randomized block design with three replications, the first factor being the established variety P-05 (V1) the cemeti variety (V2), the second factor being the spacing between 20x20 cm, 25x25. cm, 30x30 cm. Parameters observed included plant height, number of productive tillers, panicle length, weight of dry grain harvested/clump, weight of dry grain stored per clump, weight of dry grain harvested/plot, weight of stored dry grain per plot, weight of 1000 grains of grain. Data analysis using ANOVA if it has a significant effect, then it is followed by a significant difference test (DMRT) with a level of 5%. The results showed that the treatment of varietal-derived ratoons had a significant effect on phenotypic diversity. Spacing treatment had no significant effect on phenotype diversity. The combination of varietal treatment and plant spacing had no significant effect on phenotype diversity, varietal treatment with plant spacing factor had no significant interaction with the combination of ratoon ratoon ratoon hybrid seed with a spacing of 30x30 cm.